2002
DOI: 10.1590/s0066-782x2002000200005
|View full text |Cite
|
Sign up to set email alerts
|

Does a Role Exist for Tilting-Guided Therapy in the Management of Neurocardiogenic Syncope?

Abstract: Purpose -Upright tilt-table testing (UTT) is an useful method for identifying patients with neurocardiogenic syncope, but its role in the evaluation of therapeutic efficacy is controversial. The aim of this study was to determine the correlation between negative UTT after therapy introduction (acute efficacy) and symptom recurrence during follow-up (chronic efficacy). Methods -We studied 56 severely symptomatic patients (age 27±19 years) with recurrent (7±12 episodes) neurocardiogenic syncope (positive UTT). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Hachul et al 39 reported that, after the institution of the treatment for Vasovagal Syndrome, the HUTT with negative result was associated with the lower recurrence of symptoms in relation to the positive result (4.9 versus 52.4%, in 12 months, p<0.0001). Bastos et al 40 analyzed the capacity of the test to predict the recurrence of symptoms after discontinuation of medication and they found that 84% of patients with positive HUTT, under this condition, developed the symptoms again after being monitored for 12 months.…”
Section: Tilt Test In the Prognostic Evaluationmentioning
confidence: 99%
“…Hachul et al 39 reported that, after the institution of the treatment for Vasovagal Syndrome, the HUTT with negative result was associated with the lower recurrence of symptoms in relation to the positive result (4.9 versus 52.4%, in 12 months, p<0.0001). Bastos et al 40 analyzed the capacity of the test to predict the recurrence of symptoms after discontinuation of medication and they found that 84% of patients with positive HUTT, under this condition, developed the symptoms again after being monitored for 12 months.…”
Section: Tilt Test In the Prognostic Evaluationmentioning
confidence: 99%
“…As it has already been mentioned, some individuals might present symptoms of orthostatic intolerance, with changes in their brain blood perfusion which is not gauged in the regular protocol of this test whereas some others have the symptoms only due to their psychosomatic condition. The standard response during the tilt test can provide significant information for the management of these patients 32 .…”
Section: Tilt Table Testmentioning
confidence: 99%
“…The risks involved for undergoing the test is extremely low. The use of the tilt table test to evaluate the therapeutic efficacy has been controversial as observed in different series 31,32 . Several other methods have been described and are being evaluated, such as the use of sensitization agents in the first phase or shorter tests (twenty minutes) followed by pharmacological sensitization 28,33 .…”
Section: Tilt Table Testmentioning
confidence: 99%
“…The reasons being primarily the poor reproducibility of tilt testing in the long-term and the marked placebo or therapeutic effect that tilt table test has by its own. Hachul et al have previously reported a lower recurrence of syncope in treated patients with a follow-up negative tilt test compared to those that remain with inducible VVS during tilt 5 . These observations are provocative but are limited by the fact that this data was not derived from a randomized study.…”
mentioning
confidence: 96%